Calendar and cycling ageing combination of batteries in electric vehicles. (September 2018) - Redondo-Iglesias, Eduardo; Venet, Pascal; Pelissier, Serge
Abstract: The battery is the most sensitive part in the powertrain of full electric vehicles because of its cost and weight. The full electric vehicle range and prize are highly determined by the battery performances. During its lifespan, the battery performances are degraded because of ageing mechanisms. Typically, there are two types of ageing: calendar and cycling ageing. In the electric vehicle application, both types of ageing coexist and interact. In this paper, we report the results of accelerated ageing tests and present a methodology to separate calendar from cycling ageing. With this analysis method, we demonstrate the interaction between calendar and cycling ageing when battery is cycled following representative current profiles of the electric vehicle application. Highlights: Calendar ageing is dominant in electric vehicles but cycling and calendar ageing may interact. An accelerated ageing test campaign has been conducted on lithium-ion cells. A cumulative damage approach is used to separate cycling and calendar parts of ageing. Very nonlinear interactions between cycling and calendar ageing appear.